The Kambārī in the Museum of the Frankincense Land, Salalah, Oman. (23rd August 2019) - Weismann, Norbert; Dziamski, Piotr; Haar, Lilli
Abstract: This article examines the kambārī vessel now housed at the Museum of the Frankincense Land, Salalah, Oman, built for display in 1980. This sewn‐plank boat type, used for fishing and lightering in Dhofar, is discussed in the context of other similar vessels in Oman, South Yemen, and Somalia. As one of only five known surviving kambaris, a detailed account of this vessel's construction is given accompanied by an accurate pictoral record. Abstracto: La embarcación Kambārī en el Museo de la Tierra Frankincense, Salalah, Oman Este artículo examina la embarcación kambārī expuesta en el Museo de la Tierra Frankincense, Salalah, Oman y construida para su exposición en 1980. Este tipo de embarcación cosida, empleada para la pesca y el aligeramiento de otras naves en Dhofar, es discutido en el contexto de otras embarcaciones similares en Omán, el Sur de Yemen y Somalia. Al tratarse de una de las cinco embarcaciones kambaris aún existentes que se conocen, se ofrece un recuento detallado de su construcción acompañado de un registro pictórico preciso. 抽象: 阿曼塞拉莱乳香之路博物馆的"康巴里"( Kambārī ) 本文研究1980年为展示而建, 现存于阿曼塞拉莱乳香之路博物馆的"康巴里"船。本文将这一在佐法尔用于捕鱼和运输的缝制船型置于阿曼、南也门和索马里其他近似的船只背景下进行探讨。作为五艘已知现存的"康巴里"船之一, 本文还详细描述了此船的结构并附有准确的图片记录。 阿曼塞拉萊乳香之路博物館的"康巴里"(Kambārī) 本文研究1980年爲展示而建, 現存于阿曼塞拉萊乳香之路博物館的"康巴里"船。本文將這一在佐法爾用于捕魚和運輸的縫制船型置于阿曼、南也門和索馬裏其他近似的船只背景下進行探討。作爲五艘已知現存的"康巴里"船之一, 本文還詳細描述了此船的結構並附有准確的圖片記錄。 ملخص: